Thermal and shear stress-induced phenotypic changes in Bacillus paralicheniformis TB197 in submerged liquid cultures - Estefany Chavarria-Quicaño; Miguel A. Hernández-Oñate; Jorge A. Rodríguez-González; Francisco De la Torre-González; Ali Asaff-Torres (Applied Microbiology and Biotechnology)
Abstract Lipopeptides (LPs) are secondary metabolites predominantly produced by Bacillus species and have significant industrial applications. The synthesis of these compounds is regulated by quorum sensing systems, which are activated in response to abiotic stress. This study examined the impact of heat and shear stresses on the growth, LPs production, and phenotype formation of the Bacillus paralicheniformis TB197 strain in controlled submerged cultures. A differential expression analysis was performed on genes associated with phenotypes, including biofilms (tasA), motility (hag), sporulation (sspB), and the production of lipopeptides (fenB and lichA). The findings demonstrated that, under conditions of 30 °C, an increase in agitation levels from 300 to 600 rpm resulted in a 1.5-fold enhancement in cell concentration and a 2.8-fold increase in LPs production. At 40 °C, these values were 2.80- and 2.06-fold, respectively. Furthermore, fenB and lichA expression levels increased by 17- and 36-fold, respectively, suggesting that the combined stress of 40 °C and 600 rpm promotes the development of LP-producing phenotypes. However, at 45 °C, although cell concentration showed no difference compared to 40 °C, LPs production decreased 2.49-fold, with reductions in lichA (sixfold) and fenB (65-fold) expression. Under these conditions, a predominance of sporulating and biofilm-forming phenotypes was observed, supported by increased expression of tasA and sspB genes. These findings show that thermal and mechanical stresses differentially modulate the expression of phenotypes and the production of LPs in B. paralicheniformis TB197. Key points • Shear and thermal stress differentially modulate Bacillus paralicheniformis TB197 phenotypes. • Conditions of 40°C and 600 rpm induce lipopeptide-producing phenotypes, thereby optimizing their biosynthesis. • Shear and thermal stress suppress flagellate phenotypes while promoting sporulation and biofilm formation. Graphical Abstract